2013
DOI: 10.1038/msb.2013.29
|View full text |Cite
|
Sign up to set email alerts
|

Network quantification of EGFR signaling unveils potential for targeted combination therapy

Abstract: Analysis of the signaling response of colon cancer cells to systematic perturbations reveals an EGF receptor-mediated cross-talk between the MAPK and AKT pathways. Accordingly, the predicted combinatorial treatment is shown to inhibit tumor growth in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
262
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(276 citation statements)
references
References 68 publications
(117 reference statements)
11
262
0
Order By: Relevance
“…A notable absence from the Challenge was the use of mathematical, boolean or logic based mechanistic pathway modelling approaches [25][26][27][28][29] , likely due to the intensity of model creation. The dynamic nature of mechanistic models may offer an advantage by enabling consideration of the heterogeneity that exists across even apparently 'clonal' cell line populations 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A notable absence from the Challenge was the use of mathematical, boolean or logic based mechanistic pathway modelling approaches [25][26][27][28][29] , likely due to the intensity of model creation. The dynamic nature of mechanistic models may offer an advantage by enabling consideration of the heterogeneity that exists across even apparently 'clonal' cell line populations 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a number of recent studies have successfully studied logic models to investigate signaling pathways and suggest effective drug combinations which were then validated in vitro and/or in vivo 18, 19, 20, 45. Mathematical models calibrated using cell lines have also been proved effective in predicting clinical patient outcomes 82…”
Section: Resultsmentioning
confidence: 99%
“…For example, comparing signaling pathways of healthy and diseased cells allows investigating which mechanisms are deregulated as a cause or an effect of the disease 16, 17. Similarly, the comparison of pathway activity in different cells from the same cancer type allows investigating mechanism of resistance to drugs, which can be exploited to suggest personalized therapies 18, 19, 20. If experimental data are available, optimization procedures can be used to refine the initial networks to be cell line‐ or context‐specific.…”
Section: Regulatory Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…It also contributed to robustness to a MEK inhibitor during medical treatment (Sturm et al, 2010b;Fritsche-Guenther et al, 2011). For colorectal cancer cells, it was shown that the negative feedback in EGFR signaling led to cross-talk between ERK and AKT signaling; inhibition of ERK resulted in activation of AKT, via EGFR, and combined inhibition of ERK and EGFR inhibited Ras, ERK, and AKT (Sturm et al, 2010b;Klinger et al, 2013). These predictions were first made with a mathematical model before being validated with a xenograft model.…”
Section: Negative Feedback In Signal Transduction Cascades: Oscillatimentioning
confidence: 99%